If it's not what You are looking for type in the equation solver your own equation and let us solve it.
9=2(5x-3)
We move all terms to the left:
9-(2(5x-3))=0
We calculate terms in parentheses: -(2(5x-3)), so:We get rid of parentheses
2(5x-3)
We multiply parentheses
10x-6
Back to the equation:
-(10x-6)
-10x+6+9=0
We add all the numbers together, and all the variables
-10x+15=0
We move all terms containing x to the left, all other terms to the right
-10x=-15
x=-15/-10
x=1+1/2
| 5^(x+2)=125^(2x) | | 77+42+x=180 | | (5x)(4x)=500 | | 79=4x-5 | | -35-4x=-10-9x | | -6c=-12 | | 4/t+7=10 | | 7n+8n=11n | | 9b+5=4 | | 6+3y=5y+4,y= | | x+2x-4=14* | | k-(5/6)=1/6 | | 15=x/3+15 | | 5x2+7x-12=0 | | 3=-0.5(6n+6) | | 19+9r=1 | | 6x-3.2=-31.4 | | 17+45+2x=180 | | 9v-42=170-v | | 7x-2=47* | | 81=f-(-9) | | h^2-18h-19=0 | | 92+7x-2=21x+6 | | -3+5t=6t | | 4*x/5=-16 | | 9x-40=23 | | 4(2x-4)=-6 | | 30+10x+20=90 | | 50+5x+x=180 | | x+391/4=180 | | 17m–9=5 | | x+x+x+32=156-34 |